ANALISIS SIFAT KIMIA TANAH PADA DEMPLOT HUTAN TANAMAN AGROFORESTRY LOK BUNGUR DI DESA DAMIT HULU KECAMATAN BATU AMPAR KABUPATEN TANAH LAUT - Wachid Pramono; Ahmad Yamani; Damaris Payung (Universitas Lambung Mangkurat, 2022)
Soil chemical properties are very important as research object, because by examining the soil chemical properties can know where the good arable land and poor land to be connected. Chemical properties that affect soil fertility is the cation exchange capacity (CEC), the degree of acidity or pH, organic matter content, nitrogen (N), phosphorus (P),The element potassium (K), and the element magnesium (Mg), as well as elements of Calcium (Ca).The purpose of this study to analyze the content of macro nutrients (N, P, K, Ca, Mg,). The benefit is to provide scientific information data related to the content of macro nutrients on forest plots in the village agroforestry plants Damit Hulu subdistrict, Tanah Laut District Batu Ampar. Observations were made on a 3 point locations at the point provenances Solomon, provenance Sumedang and provenances Wamena. Soil sampling done by making a contour cut path. Distance point is disturbed soil sampling every 50 meters with a depth of 0-30 cm. Each observation point provenance soil sample taken 3 points less than 1 kg to be analyzed in the laboratory.The soil samples were analyzed to determine the content of macro nutrients N, P, K, Ca and Mg, the results of the analysis in the laboratory compared to the Assessment Criteria Soil Chemical Properties in the Central Research Institute Land (LPPT), Bogor. The results showed macro nutrient content of soil in three locations relative observation is not much different. N content is low. Nutrients P is classified, and K nutrients in each provenance is high. Nutrients Ca on each provenance moderate. While Mg is very low nutrient content. It is advisable to perform additional N and Mg nutrients according to plant needs. Plantation built in order to grow and develop optimally as expectedSifat kimia tanah sangat penting dijadikan objek penelitian, karena dengan meneliti sifat kimia tanah dapat mengetahui tanah mana yang baik ditanami dan tanah yang tidak baik untuk disambung. Sifat kimia yang mempengaruhi kesuburan tanah yaitu kapasitas tukar kation (KTK), derajat kemasaman tanah atau pH, kandungan bahan organik, Nitrogen (N), Fosfor (P), Unsur Kalium (K), dan Unsur Magnesium (Mg), serta Unsur Kalsium (Ca). Tujuan penelitian ini untuk menganalisis kandungan unsur hara makro (N, P, K, Ca, Mg,). Manfaatnya untuk memberikan data informasi ilmiah terkait kandungan unsur hara makro pada demplot hutan tanaman Agroforestry di Desa Damit Hulu Kecamatan Batu Ampar Kabupaten Tanah Laut.Pengamatan dilakukan pada 3 titik lokasi yaitu pada titik Provenan Solomon, Provenan Sumedang dan Provenan Wamena. Pengambilan sampel tanah dilakukan dengan membuat jalur memotong kontur. Jarak titik pengambilan sampel tanah terganggu adalah setiap 50 meter dengan kedalaman 0 – 30 cm. Setiap titik pengamatan Provenan diambil 3 titik sampel tanah kurang lebih 1 kg untuk dianalisis di laboratorium. Sampel tanah tersebut dianalisis untuk mengetahui kandungan unsur hara makro N, P, K, Ca dan Mg, hasil analisis di Laboratorium dibandingkan dengan Kriteria Penilaian Sifat Kimia Tanah menurut Lembaga Pusat Penelitian Tanah (LPPT), Bogor. Hasil penelitian menunjukkan kandungan unsur hara makro tanah di 3 lokasi pengamatan relatif tidak jauh berbeda. Kandungan N tergolong rendah. Unsur hara P tergolong sedang, dan unsur hara K di setiap Provenan tergolong tinggi. Unsur hara Ca pada setiap Provenan tergolong sedang. Sedangkan unsur hara Mg sangat rendah kandungannya. Disarankan untuk melakukan tambahan unsur hara N dan Mg sesuai dengan kebutuhan tanaman. Agar hutan tanaman yang dibangun dapat tumbuh dan berkembang secara optimal sesuai dengan yang diharapkan